English English - Ellya Rakhmawati; Wiwik Kusdaryani; Suhendri; Tri Suyati (Universitas Pendidikan Ganesha, 2022)
The outbreak of the COVID-19 pandemic has shocked countries around the world and caused a global disruption to learn. As a response to controlling the outbreak, the Indonesian government took decisive action to change the face-to-face teaching and learning process to online learning. This research aims to analyze the teacher's role in exploring the Merdeka curriculum for early childhood education in kindergarten. This type of research is qualitative with a qualitative phenomenological study design. Data collection was carried out from documentation and in-depth interviews with participating teachers. Data collection instrument with a questionnaire. The data analysis technique uses descriptive qualitative analysis. The study results, namely five findings, were found from teacher participants. The teacher allows students to determine the learning theme as the learning material. In addition, teachers will create lesson plans for their daily routines and learning modules. The teacher arranges activities based on learning modules. Teachers' awareness of technology must be increased to support the learning process. In addition, parents must also accompany and look after their children while playing and study.